СТРАТЕГІЧНЕ ПАРТНЕРСТВО У СФЕРІ ОСВІТНІХ ПОСЛУГ: НОВІ ВИМІРИ ВЗАЄМОДІЇ (Регіональні аспекти розвитку продуктивних сил України, 2024)
АНОТАЦІЯВступ. Стратегічне партнерство у сфері освітніх послуг набуває особливої актуальності в контексті глобалізації, технологічних та інноваційних змін, зокрема у процесах післявоєнного відновлення і потреби в адаптивних системах освіти. Сучасні виклики, такі як стрімкий розвиток диджиталізації, зміни на ринку праці та глобальні соціально-економічні трансформації, вимагають від закладів освіти нових підходів до вибудови не лише взаємовідносин, взаємодії та співпраці, а й стратегічного партнерства з бізнес-структурами та державними і міжнародними інституціями. Створення стратегічних партнерств між закладами освіти та науки, бізнесом, державними органами і міжнародними організаціями сприятиме забезпеченню інтеграції ресурсів, знань та інновацій, що, своєю чергою,  впливатиме на якість освітніх послуг, їх відповідність вимогам сучасного суспільства та національну безпеку. Мета. Дослідження сучасних підходів та оцінювання нових вимірів взаємодії між різними учасниками стратегічного партнерства у сфері освітніх послуг.Методи. Наукові методи дослідження: аналіз літературних джерел та аналітичних звітів із досліджуваної проблематики, успішних практик державно-приватного і стратегічного партнерства «наука – бізнес – освіта» для формування ефективних стратегій учасників таких партнерств і їх адаптації до українських умов; порівняння та узагальнення – для здійснення понятійного аналізу та структуризація форм і рівнів взаємодії між суб’єктами: від пошуку партнерів до стратегічного партнерства; системний підхід, що передбачає розробку критеріїв і методів для оцінювання результативності стратегічних партнерств у сфері освіти й узгодження інтересів та цілей сторін у досягненні взаємовигідних результатів, зокрема отриманні вигод закладів освіти/науки, держави та бізнес-організацій від реалізації стратегічного партнерства.Результати. У статті проаналізовано різні підходи до тлумачення понять «стратегічне партнерство», «партнерство», «взаємовідносини», «співпраця», «кооперація», «взаємодія», які можуть різнитися залежно від суб’єктного складу та сфери застосування. Враховуючи це, розроблено графічну модель розвитку міжорганізаційних зв’язків від етапу вибору потенційного партнера до вибудови з ним партнерських взаємовідносин, а у подальшому − стратегічного партнерства. Доведено, що вибудова взаємовідносин є складним процесом, який не має чітко визначеного часового виміру, і такі взаємовідносини можуть починатися з разової взаємодії і за наявності сприятливого досвіду з обох сторін поступово перетворюватися на партнерські. У цьому контексті стратегічне партнерство виникає у разі збігу стратегічних інтересів у конкретних сферах взаємовідносин партнерів, при цьому динамізм стратегічного партнерства залежить від наявних стратегічних ресурсів суб’єктів. Вибудова стратегічного партнерства у сфері освіти ґрунтується на принципах узгодження стратегічних цілей, бачення та отримання взаємовигоди у довгостроковій перспективі ключових учасників: закладів освіти/науки («Освіта/Наука»), бізнес-структур («Бізнес») і державних інституцій. При цьому вибудова і посилення стратегічного партнерства між зазначеними учасниками передбачає отримання певних стратегічних вигод, і не лише фінансових.Висновки. Поняття «партнерство» має мультидисциплінарний характер, з варіативними тлумаченнями, що залежать від суб’єктного складу та сфери застосування. Стратегічне партнерство означає формування взаємин між організаціями для досягнення спільних стратегічних цілей через інтеграцію ресурсів, знань і технологій, що забезпечує сталий розвиток та отримання взаємних вигод. Взаємодія і взаємовідносини між учасниками стратегічного партнерства є складним і тривалим процесом, у підґрунті якого є довіра, спільні інтереси та координація дій для досягнення спільних цілей, що може передбачати еволюцію від разових контактів до глибоких, тривалих партнерських відносин. Основні принципи, які регулюють стратегічне партнерство у сфері освітніх послуг, охоплюють взаємовигоду, комунікацію, етичність та доброчесність у відносинах між партнерами, включаючи залучення нових моделей співпраці з бізнесом та державними установами, що є важливими для успішного розвитку і сталості партнерств. Отже, реалізація стратегічних партнерств може позитивно впливати на економічний розвиток, підвищуючи якість освітніх послуг та конкурентоспроможність країни, особливо в умовах післявоєнного відновлення, що підкреслює важливість системного та стратегічного підходу до формування партнерських відносин у сфері освіти відповідно до сучасних вимог та викликів.Ключові слова: взаємовідносини, взаємодія, співпраця, кооперація, партнерство, стратегічне партнерство, розвиток, вигоди, сфера освіти. ABSTRACTIntroduction. Strategic partnerships in the field of educational services are becoming particularly relevant in the context of globalization, technological and innovative changes, especially in the processes of post-war recovery and the need for adaptive education systems. Modern challenges, such as the rapid development of digitalization, changes in the labor market, and global socio-economic transformations, require educational institutions to adopt new approaches not only to building relationships, interactions, and cooperation but also to establishing strategic partnerships with business structures, as well as state and international institutions. The creation of strategic partnerships between educational and research institutions, business, governmental bodies, and international organizations will facilitate the integration of resources, knowledge, and innovations, which in turn will impact the quality of educational services, their compliance with the demands of modern society, and national security.Goal. Research of Modern Approaches and Evaluation of New Dimensions of Interaction Among Various Participants in Strategic Partnerships in the Field of Educational Services.Methods. Scientific Research Methods: Analyzing literary sources and analytical reports related to the research problem, as well as successful practices of public-private and strategic partnerships in the “science – business – education” nexus, to formulate effective strategies for the participants in such partnerships and adapt them to the Ukrainian context; comparison and generalization for conceptual analysis and structuring of forms and levels of interaction among subjects, from partner search to strategic partnership; a systemic approach that involves developing criteria and methods for evaluating the effectiveness of strategic partnerships in the field of education and aligning the interests and goals of the parties to achieve mutually beneficial outcomes, particularly ensuring advantages for educational/research institutions, the state, and business organizations from the implementation of strategic partnerships.Results. The article analyzes various approaches to interpreting the concepts of “strategic partnership”, “partnership”, “relationships”, “cooperation”, “collaboration”, and “interaction”, which may vary depending on the composition of participants and the field of application. In light of this, a graphical model has been developed to illustrate the evolution of interorganizational relationships from the stage of selecting a potential partner to building partnership relations and subsequently to strategic partnership. It is demonstrated that building relationships is a complex process that does not have a clearly defined time frame, and such relationships may begin with one-time interactions and gradually transform into partnerships, provided there is a favorable experience on both sides. In this context, strategic partnership arises when there is a convergence of strategic interests in specific areas of the partners' relationships, while the dynamism of strategic partnership depends on the available strategic resources of the participants. The establishment of strategic partnerships in the field of education is based on the principles of aligning strategic goals, visions, and achieving mutual benefits in the long term among key participants: educational and research institutions (“Education/Science”), business structures (“Business”), and government institutions (“State”). At the same time, the establishment and strengthening of strategic partnerships among these participants implies the realization of certain strategic benefits, not only financial.Conclusions. The concept of “partnership” has a multidisciplinary nature, with various interpretations that depend on the composition of participants and the field of application. Strategic partnership refers to the establishment of relationships between organizations aimed at achieving common strategic goals through the integration of resources, knowledge, and technologies, which ensures sustainable development and mutual benefits. The interaction and relationships among participants in a strategic partnership constitute a complex and long-term process, underpinned by trust, shared interests, and coordinated actions towards achieving common objectives, which may involve an evolution from one-time contacts to deep, lasting partnerships. The main principles governing strategic partnerships in the field of educational services include mutual benefit, communication, ethics, and integrity in relations between partners, as well as the involvement of new models of collaboration with businesses and government institutions, all of which are essential for the successful development and sustainability of partnerships. Therefore, the implementation of strategic partnerships can have a positive impact on economic development by enhancing the quality of educational services and the competitiveness of the country, especially in the context of post-war recovery, which underscores the importance of a systematic and strategic approach to forming partnership relations in the field of education in accordance with modern demands and challenges.Keywords: relationships, interaction, cooperation, collaboration, partnership, strategic partnership, development, benefits, education sector.